Voluntary regulation of NGOs and nonprofits : an accountability club framework - Gugerty, Mary Kay.; Prakash, Aseem (Cambridge : Cambridge University Press, 2010)
How can nonprofit organizations and NGOs demonstrate to resource providers, regulators and stakeholders that they are using their funds appropriately and delivering on their promises? This volume examines the emergence, design and effectiveness of accountability clubs as standard-setting institutions designed to respond to this challenge.
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Finance